2017
DOI: 10.5194/acp-17-11075-2017
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling fast and slow responses of the East Asian summer monsoon to reflecting and absorbing aerosol forcings

Abstract: Abstract. We examine the roles of fast and slow responses in shaping the total equilibrium response of the East Asian summer monsoon (EASM) to reflecting (sulfate, SO 4 ) and absorbing (black carbon, BC) aerosol forcings over the industrial era using the Community Earth System Model version 1 (CESM1). Our results show that there is a clear distinction between fast and slow responses of the EASM to aerosol forcings and the slow climate response due to aerosol-induced change in sea surface temperature (SST) play… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 52 publications
6
24
0
Order By: Relevance
“…Like other climatic variables, changes in the surface horizontal wind vector due to the reduction of PM 2.5 are very similar under RCP4.5 and RCP8.5 (Figures 9a and 9c). Enhancement of surface wind vectors from ocean to land is predicted over East Asia, as is the 10.1029/2019EF001285 cross-equatorial flow over the Indian Ocean; these results are consistent with those of previous studies (Wang, Lin, et al 2017; Figure 7. Figure 10 shows changes in low cloud cover (above 680 hPa), middle cloud cover (between 440 and 680 hPa), high cloud cover (below 440 hPa), and total cloud cover (TCC; sum of the low, middle, and high cloud fractions) due to changes in fine particles, and changes in TCC caused by coarse particles under RCP4.5 and RCP8.5 from 2014 to 2050.…”
Section: Atmospheric Circulationsupporting
confidence: 92%
See 1 more Smart Citation
“…Like other climatic variables, changes in the surface horizontal wind vector due to the reduction of PM 2.5 are very similar under RCP4.5 and RCP8.5 (Figures 9a and 9c). Enhancement of surface wind vectors from ocean to land is predicted over East Asia, as is the 10.1029/2019EF001285 cross-equatorial flow over the Indian Ocean; these results are consistent with those of previous studies (Wang, Lin, et al 2017; Figure 7. Figure 10 shows changes in low cloud cover (above 680 hPa), middle cloud cover (between 440 and 680 hPa), high cloud cover (below 440 hPa), and total cloud cover (TCC; sum of the low, middle, and high cloud fractions) due to changes in fine particles, and changes in TCC caused by coarse particles under RCP4.5 and RCP8.5 from 2014 to 2050.…”
Section: Atmospheric Circulationsupporting
confidence: 92%
“…The Monte Carlo Independent Column Approximation (McICA) scheme developed by Räisänen et al (2004) was applied to the model to resolve subgrid cloud variability. Previous studies have shown that this model simulates aerosol mass concentrations, optical properties, and climatology well Yang et al, 2016Yang et al, , 2017. The model has been used to study radiative forcing due to aerosols (Bond et al, 2013;Myhre et al, 2013;Wang, Zhang, Li, et al 2013;Zhang et al, 2012Zhang et al, , 2016 and its effects on climate Zhang et al, 2016;Zhao et al, 2017;Zhou et al, 2017).…”
Section: Modelmentioning
confidence: 91%
“…This study highlights the important role of anthropogenic aerosols in the interdecadal variations in UTT over East Asia. This may from a side imply that aerosol forcing affects the EASM by changing the thermodynamic structure in the upper troposphere rather than at the surface, as reported by Z. L. Wang, Lin, Yang, et al (2017). However, it should be noted that the aerosol-induced JA mean UTT trend over East Asia during the second half of the twentieth century is weaker than that of the reanalysis data ensemble mean (i.e., −0.14 vs. −0.2°C per decade).…”
Section: Discussionmentioning
confidence: 79%
“…There are significant positive stream function anomalies south of 40°N, with slight negative values between 10°N and 20°N, which lead to two anomalous clockwise meridional circulations, south of 20°N and between 20°N and 40°N, respectively. The aerosol-induced change in meridional circulation may be primarily attributed to the slow response of the ocean to aerosol forcing, that is, the asymmetric hemispheric change in SST (Ocko et al, 2014; Z. L. Wang, Lin, Yang, et al, 2017;Xu & Xie, 2015). However, there are negative stream function and counterclockwise circulation anomalies between 40°N and 70°N.…”
Section: 1029/2018ef001052mentioning
confidence: 99%
See 1 more Smart Citation